2014
DOI: 10.1097/inf.0000000000000260
|View full text |Cite
|
Sign up to set email alerts
|

Management of Latent Tuberculosis Infection in Child Contacts of Multidrug-Resistant Tuberculosis

Abstract: After exposure to a teacher with multidrug-resistant pulmonary tuberculosis, 31 children developed latent infection. Twenty-six were treated with levofloxacin and pyrazinamide. Twelve required a change in therapy secondary to adverse effects. The most common adverse effects included abdominal pain, arthralgias/myalgias and elevated transaminases. All children reported at least 1 adverse effect. Fifteen children completed treatment. All adverse effects were transient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 8 publications
1
27
0
Order By: Relevance
“…Pyrazinamide is excluded, given the substantial toxicity and high rates of discontinuation reported in observational studies where the drug was used [58][59][60]. For contacts of MDR-TB plus fluoroquinolone resistance cases with low-level isoniazid resistance, some authors suggest the use of high-dose isoniazid [61], however there is no evidence to support this approach.…”
Section: Preventive Therapymentioning
confidence: 99%
“…Pyrazinamide is excluded, given the substantial toxicity and high rates of discontinuation reported in observational studies where the drug was used [58][59][60]. For contacts of MDR-TB plus fluoroquinolone resistance cases with low-level isoniazid resistance, some authors suggest the use of high-dose isoniazid [61], however there is no evidence to support this approach.…”
Section: Preventive Therapymentioning
confidence: 99%
“…After combining data from the comparison studies of Adler-Shohet et al [22], Bamrah et al [19], Denholm et al [20], Schaaf et al [21], and Williams et al [23], we found a statistically significant reduction in TB incidence among treated vs untreated persons (Figure 2). The reduction in MDR TB incidence was found using several methods (a 91%–92% risk reduction controlling for person-time using Poisson regression alone or controlling for zero inflation and random effects) to analyze count data with multiple zero outcomes.…”
Section: Resultsmentioning
confidence: 75%
“…Of the 6 comparison studies, all but Bamrah et al [19] (Micronesia) and Schaaf et al [21] (South Africa) were conducted in countries having low TB incidence: Adler-Shohet et al [22] (United States), Attamna et al [7] (Israel), Denholm et al [20] (Australia), and Williams et al [23] (United Kingdom). Among the studies in low-incidence settings, only Denholm et al reported any TB cases (2/49 [4%] study subjects) after 2–6 years following treated and untreated persons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies demonstrate serious adverse effects associated with the use of pyrazinamide in combination with either ethambutol ( 10 ) or a fluoroquinolone, including ofloxacin ( 11 , 12 ) and levofloxacin ( 13 , 14 ). However, a recent study of contacts treated with moxifloxacin- or levofloxacin-based prophylaxis found no serious adverse events and fewer cases of disease among those treated than those untreated ( 15 ).…”
Section: Discussionmentioning
confidence: 99%